2022
DOI: 10.1039/d1nj05633f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a CoO–ZnO photocatalyst for enhanced visible-light assisted photodegradation of methylene blue

Abstract: The synthesis of efficient photocatalysts for visible light-assisted photodegradation of aqueous phase organic pollutants has received significant consideration recently. In this research, Co-doped ZnO is synthesized by precipitation method for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 62 publications
4
23
0
Order By: Relevance
“…Compared to pristine 1.5Au-PCN, the Y ZIF/1.5Au-PCN nanocomposites have improved the photocatalytic activities for conversion of CO 2 (Figure A) and BPA decontamination (Figure B). As expected, the 3ZIF/1.5Au-PCN sample showed the highest photocatalytic activities …”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Compared to pristine 1.5Au-PCN, the Y ZIF/1.5Au-PCN nanocomposites have improved the photocatalytic activities for conversion of CO 2 (Figure A) and BPA decontamination (Figure B). As expected, the 3ZIF/1.5Au-PCN sample showed the highest photocatalytic activities …”
Section: Resultssupporting
confidence: 83%
“…As expected, the 3ZIF/ 1.5Au-PCN sample showed the highest photocatalytic activities. 41 Moreover, the time base activity curves given in Figure S3A showed that all samples are the most active up to 1.5 h. These results confirmed that our synthesized material has important activities for organic BPA decontamination and CO 2 conversion to valuable products.…”
Section: Exploring the Importance Of A Mof (Zif-67)supporting
confidence: 76%
“…BA-5 and BA-10 had a high photocatalytic property, and their degradation rate of RhB was up to 99.9% in 60 min, whereas the degradation rates of pure Bi2MoO6 (pH = 9) and Ag2CrO4 were only 22.0%, and 53.8%, respectively. Figure 13b shows the linear relationship between −ln(C/C0) and t, the degradation curve of RhB was consistent with the pseudo-first-order kinetic equation [64,65]. The degradation rate constant kap of BA-5 was 0.07857 min −1 , which was 24.63 times of pure Bi2MoO6 and 6.44 times of pure Ag2CrO4.…”
Section: Investigation Of Photocatalytic Propertiessupporting
confidence: 71%
“…7,8 In this regard, development of visible light responsive photocatalytic composites can be an attractive alternative to eliminate the high energy demand. Different types of semiconductor materials and composites, like composite metal oxides, 9–13 metal carbides, 14,15 metal sulfides, 8,16 graphene derivatives, 17 graphitic carbon nitride, 18–21 metal organic frameworks (MOFs), 22–24 MXene, 25 etc. , have been employed as highly effective photocatalysts in the removal of various contaminants in water.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In this regard, development of visible light responsive photocatalytic composites can be an attractive alternative to eliminate the high energy demand. Different types of semiconductor materials and composites, like composite metal oxides, [9][10][11][12][13] metal carbides, 14,15 metal sulfides, 8,16 graphene derivatives, 17 graphitic carbon nitride, [18][19][20][21] metal organic frameworks (MOFs), [22][23][24] MXene, 25 etc., have been employed as highly effective photocatalysts in the removal of various contaminants in water. To increase the harvesting of visible light irradiation, lowering the excited e À /h + recombination, as well as introducing more reactive sites for photocatalytic reactions, formation of heterojunctions between different visible light responsive semiconductors is a viable option.…”
Section: Introductionmentioning
confidence: 99%